(untitled) (Research, Society and Development, 2022)
The article aims to identify the maturity level of Local Productive Arrangements, in Serra Gaúcha, in Rio Grande do Sul, made up of micro, small and medium-sized companies, which have a set of specific characteristics among themselves, in the specialization of products / processes / technologies. A process, in which, the Arrangements rely on public policies, in the organization and structuring of governance, to qualify the technical capacity of the actors, stimulating endogenous potentialities, activating the local associative movement, becoming a fertile environment, to check the level of maturity of the Arrangements. To answer this challenge, the research uses Pietrobon’s (2009) maturity level identification model. Still, the study counts on the results collected, through the questionnaire, which presents the mapping and standardization of processes, training, organizational structure, continuous improvement, relationship, certification, partnerships, organizational climate and information technology, strategic planning. Through the lenses of Pietrobon (2009), the maturity degrees of each Arrangement were established, bearing in mind the analysis by dimension, building an equivalence between research data, which allowed the identification of the maturity degree, highlighting in the first place, the Metalmechanic and Automotive, in second, the Polo de Moda, in third, the Furniture. Still, the research points out that the Local Productive Arrangements are mechanisms for the development of the productive sector, especially, as it has the financing and structuring power of the State, which models, assists in the organization of the Arrangement. However, the local human factor, the commitment of the members, which modifies and matures the Arrangement is decisive.